214k views
5 votes
Solve -(10x + 1) + 4(x- 1) = -23

User Shanikqua
by
5.9k points

2 Answers

6 votes
x=3

1. distribute the negative.
2. subtract the numbers
3. combine like terms
4. add five to both sides of the equation
5. simplify
6. divide both sides of the equation by the same term
7. simplify again :)

have a good day
User Ravindra Ranwala
by
6.0k points
4 votes

Answer:

x = 3

Explanation:

  • -(10x + 1) + 4(x- 1) = -23 expand
  • -10x - 1 + 4x - 4 = -23 combine similar terms
  • -10x + 4x = -23 + 1 + 4 simplify
  • -6x = -18 divide -6 both sides
  • x = -18 / -6 simplify
  • x = 3
User Mbpaulus
by
5.7k points